2010
DOI: 10.1111/j.1753-0407.2010.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self‐reported self‐esteem in healthy and diabetic children and adolescents in Greece

Abstract: Background:  The aim of the present study was to evaluate any possible negative effect of diabetes on the self‐esteem of children and adolescents with diabetes. Methods:  Self‐esteem was evaluated using the Culture‐Free Self‐Esteem Inventory (CFSEI‐2) in 144 patients with Type 1 diabetes mellitus (T1DM; 7–18 years of age) treated in a diabetes center and compared against that of 136 healthy children and adolescents. Results:  Self‐esteem was correlated with age (P = 0.017), but not with diabetes (P = 0.886). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…This may be due to chronic stress factors and short duration of the disease, which may not allow depression and anxiety to decrease with PA. Consistent with previous studies (18)(19)(20), there was no relationship between PA level and self-esteem in adolescents with T1DM, reflecting the possibly limited contribution of PA level to them regarding a balance among social acceptance, social devaluation, and rejection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may be due to chronic stress factors and short duration of the disease, which may not allow depression and anxiety to decrease with PA. Consistent with previous studies (18)(19)(20), there was no relationship between PA level and self-esteem in adolescents with T1DM, reflecting the possibly limited contribution of PA level to them regarding a balance among social acceptance, social devaluation, and rejection.…”
Section: Discussionsupporting
confidence: 90%
“…In adolescents with T1DM, compared to healthy controls, previous studies reported higher depressive symptoms (41), while another study found no differences in depressive and anxiety symptoms (42). Moreover, previous studies found that adolescents with T1DM reported higher physical abilities score and similar scores for self-esteem, physical appearance, and general self-concept, compared to healthy controls (18)(19)(20). In line with precedent mentioned findings, the present study revealed no difference in depression and anxiety levels, and self-esteem between adolescents with T1DM and healthy controls, indicating that these patients might adapt well to the disease.…”
Section: Discussionmentioning
confidence: 94%
“…Carrol et al (28) found, in a study of 125 women with diabetes, the connection between dissatisfaction with one's self-image and a lower level of self-esteem. Vlachioti et al (29), however, not found such connection and also did not find the influence of diabetes on physical activity.…”
Section: Resultsmentioning
confidence: 87%
“…Several comparative studies between children with diabetes and controls reported encouraging results. Greek children with diabetes exhibited high self-esteem, similar to that of the healthy control group (9). Furthermore, in a Turkish study, children with diabetes reported higher self-esteem scores than the control group (10).…”
Section: Introductionmentioning
confidence: 83%